Citizenship on the move: The deprivation and restoration of emigrants' hukou in China - LIU, Jiaqi M. (Institutional Knowledge at Singapore Management University, 2021)
Scholars have long debated whether international migration impinges on states’ control over transborder populations. In this article, I lay bare how states consolidate control through the calculated manipulation of emigrant citizenship. Based on a genealogical interrogation of China’s emigrant citizenship policies from the 1950s to present and three months of fieldwork in an emigrant community in China, I illustrate that the state first revokes emigrants’ citizenship and then imposes selective conditions on its restoration upon their return. China’s otherwise domestically oriented citizenship regime, namely, the household registration (hukou) system, works similarly as an international immigration regime by selecting and documenting potential citizens. My study sheds new light on the understudied external control of the hukou system by examining how it limits emigrants’ right of resettlement and proscribes overseas dual residency. I argue that citizenship is anything but an enduring, unproblematic demographic fact. It is, in essence, a revocable, precarious politico-legal accomplishment. These malleable processes enable the state to redefine the citizenship of absent and returned members, reinsert the congruence between nationality and residency, and reinforce control over transborder populations. These findings may have implications for similar mechanisms of governing international migrants through documentation and legal codification beyond China.